Social and psychological factors underlying adult vaccination behavior: lessons from seasonal influenza vaccination in the US and the UK. (August 2013) - Wheelock, Ana; Thomson, Angus; Sevdalis, Nick
This article reviews the evidence base on the social and psychological factors that facilitate or hinder vaccination among adults. The authors categorized these factors into eight themes: social influence, disease-related factors, vaccine-related factors, habit, general attitudes toward health and vaccines, awareness and knowledge, practical barriers and motivators and altruism. Although there were many commonalities between both settings, the authors also indentifiedimportant differences. A better understanding of social and psychological aspects of vaccination across contexts and vaccines remains a priority.